Theory of Cryptography 14th International Conference, TCC 2016-B, Beijing, China, October 31-November 3, 2016, Proceedings, Part I - Hirt, Martin; Smith, Adam (Security and Cryptology ;, 2016)
The two-volume set LNCS 9985 and LNCS 9986 constitutes the refereed proceedings of the 14th International Conference on Theory of Cryptography, TCC 2016-B, held in Beijing, China, in November 2016. The total of 45 revised full papers presented in the proceedings were carefully reviewed and selected from 113 submissions. The papers were organized in topical sections named: TCC test-of-time award; foundations; unconditional security; foundations of multi-party protocols; round complexity and efficiency of multi-party computation; differential privacy; delegation and IP; public-key encryption; obfuscation and multilinear maps; attribute-based encryption; functional encryption; secret sharing; new models.